The pendular mechanism does not determine the optimal speed of loaded walking on gradients - Gomeñuka, Natalia Andrea; Bona, Renata Luisa; Rosa, Rodrigo Gomes da; Peyré-Tartaruga, Leonardo Alexandre (Human movement science, 2016)
n/a
n/a